Overview of future internet: named data networking - Hussaini, Muktar; Awang Nor, Shahrudin; Ahmad, Amran (2019)
Recent development in mobile technology makes data traffic intensifies, due to the vast devices’ connectivity. Also, increases the needs for efficient and scalable distribution of data and services over the Internet. Therefore, the Information Centric Networking paradigm was proposed, with different approaches as a clean-slate redesign of current host-centric Internet architecture. It evolved to access data independent from its location, by replacing IP addresses with content named. This paper reviews the most popular Information Centric Networking approaches, called Named Data Networking which is a clean-slate Internet architecture proposed to replace IP with hierarchical named content that utilizes route aggregation to improve scalability and support mobility. In this paper, NDN is reviewed and summarized some of its features, such as naming, routing, caching and mobility support. In addition, the modes of operations based on named resolution services and named based routing for the approach with some exemplary diagrams were presented. Also, mobility supports for consumer, and challenges from current to feature Internet were discussed for future research.